2023
DOI: 10.3390/ijerph20032740
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Aging in Place among Community-Dwelling Older Adults in Korea: Findings from a National Survey

Abstract: Ever since baby boomers started turning 65 years old in 2020, Korea is set to become a super-aged society by 2025. This makes it the world’s fastest-aging society. Aging in place (AIP) has become a policy direction to prepare for an aging society and improve older adults’ quality of life. It refers to the ability of older adults to remain in their homes and communities as they age, allowing them to reside in their place of preference and access the services they require to promote their quality of life. A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Solutions such as adapting public housing to facilitate AIP, increasing financial assistance and subsidies, and providing door-to-door escorted transportation and outreach services will enable more elders to age in place. These findings align with existing research that identifies similar practical challenges commonly observed in AIP studies, especially in densely populated Asian regions that lack social security systems with generous protections and benefits [61,62]. As a matter of fact, these challenges are directly relevant to several Sustainable Development Goals: SDG 11 (Sustainable Cities and Communities), which advocates for accessible transport and affordable housing; SDG 1 (No Poverty), which includes initiatives related to financial assistance, poverty prevention, and pension schemes; and SDG 10 (Reduced Inequalities), which emphasizes social protection and participation [63].…”
Section: Discussionsupporting
confidence: 89%
“…Solutions such as adapting public housing to facilitate AIP, increasing financial assistance and subsidies, and providing door-to-door escorted transportation and outreach services will enable more elders to age in place. These findings align with existing research that identifies similar practical challenges commonly observed in AIP studies, especially in densely populated Asian regions that lack social security systems with generous protections and benefits [61,62]. As a matter of fact, these challenges are directly relevant to several Sustainable Development Goals: SDG 11 (Sustainable Cities and Communities), which advocates for accessible transport and affordable housing; SDG 1 (No Poverty), which includes initiatives related to financial assistance, poverty prevention, and pension schemes; and SDG 10 (Reduced Inequalities), which emphasizes social protection and participation [63].…”
Section: Discussionsupporting
confidence: 89%
“…Common determinants include freedom, autonomy, and social connectedness ( Ratnayake et al, 2022 ). Aging in place is associated with a sense of identity, attachment, social connection, familiarity, and security ( Cho & Kwon, 2023 ; Wiles et al, 2012 ) corroborated in this study. A social motive that is explicitly found in this study is the societal expectation of children to take care of their parents in old age, which is uncommon in western countries and has been less reported in studies.…”
Section: Discussionsupporting
confidence: 83%
“…In 2025, South Korea is entering an ultra-aged society where the elderly population comprises over 25% of the total population. 1 Major health threats to the elderly include chronic conditions such as hypertension, diabetes, cardiovascular diseases, and arthritis, as well as cognitive impairments like dementia and depression. 2 Among these, dementia stands out as a debilitating condition, primarily afflicting the elderly.…”
Section: Introductionmentioning
confidence: 99%